Tweet Sixteen and Pregnant: Missing Links in the Causal Chain from Reality TV to Fertility. A replication study of Kearney & Levine (American Economic Review, 2015) - David A. Jaeger; Theodore J. Joyce; Robert Kaestner (International Journal for Re-Views in Empirical Economics (IREE), 2019)
We replicate and extend the analysis of the positive association between social media (Google searches and tweets) and the MTV program 16 and Pregnant recently published by Melissa Kearney and Phillip Levine (2015). We find that the relationship disappears or even turns negative when we include in the analysis periods when new episodes of 16 and Pregnant were not being broadcast. The results are also sensitive to the use of weights. Our results cast substantial doubt on social media as a link in the causal chain between reality television and fertility.
http://dx.doi.org/10.15456/iree.2018226.082216
Keywords: J13; L82; C81; 330; social media; fertility; birth control; abortion; 16 and Pregnant; event study; replication study